Development and test of an electric precision seeder for small-size vegetable seeds - Jin, Xin; Li, Qianwen; Zhao, Kaixuan; Zhao, Bo; He, Zhitao; Qiu, Zhaomei (International Journal of Agricultural and Biological Engineering, 2019)
An electric seeder for small-size vegetable seeds was designed based on the power drive and the optical fiber detection technology. The seeder is driven by electric power during the sowing process. At the same time, using the fiber sensor technology to monitor the sowing condition, the seeder is more efficient with high seeding precision in terms of different seed sizes. In order to achieve the precision seeding for the 2-10 mm seeds, the driving motor is equipped in the rear crackle. The power drive reduces pollution and dyeing. Also the other components of the electric seeder were modularly designed. The seeder was designed with buckle, which could be quickly disassembled on the sowing machine to replace the sowing wheel. It can quickly adjust row spacing and sowing depth during sowing process to meet the requirements of agricultural planting. Field test was carried out for coriander, pakchoi, and radish on the accuracy and monitoring of the system, respectively. The results showed that during the field operation, the sowing precision of the sowing machine was 95%. When the seeder worked at the speeds of 3 km/h and 4 km/h, the relative error of the monitoring precision of the system was less than 6%. This system can meet the real-time monitoring requirements of the seed metering device and improve the quality of the sowing work. Keywords: precision seeding, electric seeder, nest eyed sowing wheel, electric power drive, field test, vegetable seed DOI: 10.25165/j.ijabe.20191202.4618 Citation: Jin X, Li Q W, Zhao K X, Zhao B, He Z T, Qiu Z M. Development and test of an electric precision seeder for small-size vegetable seeds. Int J Agric & Biol Eng, 2019; 12(2): 75–81.